Thermal-driven coordination adaption of metal sites in layered double hydroxides towards high-performance water oxidation. (December 2021) - Qiao, Wen; Ding, Peng; Pan, Jing; Yan, Shiming; Wang, Dunhui; Xu, Xiaoyong
Abstract: Oxygen evolution reaction (OER) is very important and even decisive in many electrochemical energy storage/conversion technologies, with an urgent need for cost-efficient catalysts to promote its kinetic behavior. Here, we synthesized a unique hybrid catalyst characterized by ultrafine cobalt/iron mixed oxide domains embedded in two-dimensional (2D) monolayer hydroxides through thermal reconstruction of layered double hydroxide precursors, which exhibits excellent OER performance in alkaline media, much superior to state-of-the-art iridium oxide catalyst. In addition to the structural advantages, the chemical coordination evolution was found to achieve metal electronic tuning in favor of intrinsic activity, and in-situ bond hydroxyl groups beneficial to conductivity and hydrophilicity, contributing together to OER kinetics. Coordination adaption of transition metal sites suggests an intuitive active-site descriptor with high-covalent transition metal-oxy-hydroxyl coordination. This work not only renders a cost-effective OER catalyst, but also provides a universal guideline for transition metal site activation. Graphical Abstract: Refined thermalization driven coordination transformation of transition metal sites in layered double hydroxides enables high-performance oxygen evolution reaction. ga1 Highlights: Record-high OER activity with robust stability is achieved in alkaline media. Coordination adaption of metal sites identifies an intuitive active-site indicator. Thermal exfoliation favors to diversify topologies from LDHs toward catalysis.